Potential Local Physics Based Learning of Jepara District To Improve Science Process Skills and Students Entrepreneurship - Ahmad Khoiri; Almira Syifa; Nurul Mubin (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2018)
Physics-based learning of local potentials on simple plan materials as a source of learning the art of carving through levers, incline, pulley and wheel pivot, learning that equip knowledge about the potentials become benchmarks and reference in developing Jepara regency. Design research using One Group Pretest-Postest Design.analysis included: normality and homogeneity, t-test hypothesis and gain test. Based on the result of t-test (thitung<ttabel = 0.0057 <2,00) there is difference of Science Process Skillsbefore and after physics learning based on local potency and gain test result there is an increase of 0.347 is moderate category. In the aspect of entrepreneurship spirit obtained an average of 83.3% good category, local Potential has been studied raises the spirit of fanaticism and high loyalty to a strong sense of ownership so as to contribute positively to the Science Process Skillsand entrepreneurial enthusiasm of learners through indicators: confidence ; task-oriented and results; dare to take risks; spirited leadership; thinking toward outcomes (benefits) and originality